2021
DOI: 10.21037/atm.2020.02.38
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary phase hypointensity on gadobenate dimeglumine- enhanced magnetic resonance imaging may improve the diagnosis of hepatocellular carcinoma

Abstract: Background: To determine the clinical value of hepatobiliary phase (HBP) hypointensity for noninvasive diagnosis of hepatocellular carcinoma (HCC). Methods: A total of 246 high-risk patients with 263 selected nodules (126 HCCs, 137 non-HCCs) undergoing gadobenate dimeglumine (Gd-BOPTA)-enhanced magnetic resonance imaging (MRI) were included in the study. Imaging-based diagnoses of small (≤3 cm) and large (>3 cm) HCCs were made using the following 4 criteria: (I) non-rim arterial phase hyper-enhancement (APHE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Among the AFs, some speci c AFs show good performance in the diagnosis of HCC [21,22].The nodule-in-nodule feature is a typical manifestation of tumour heterogeneity, and it is a variant of the "mosaic" architecture of HCC [23]. The development of most HCCs in patients with cirrhosis occur via a multistep process of carcinogenesis, from a regenerative nodule (RN) to a DN and nally to HCC [24].…”
Section: Discussionmentioning
confidence: 99%
“…Among the AFs, some speci c AFs show good performance in the diagnosis of HCC [21,22].The nodule-in-nodule feature is a typical manifestation of tumour heterogeneity, and it is a variant of the "mosaic" architecture of HCC [23]. The development of most HCCs in patients with cirrhosis occur via a multistep process of carcinogenesis, from a regenerative nodule (RN) to a DN and nally to HCC [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that some special AFs contribute to the diagnosis of HCC [ 21 , 22 ]. The nodule-in-nodule feature, a variant of the “mosaic” architecture of HCC, is a typical manifestation of tumour heterogeneity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gadobenate dimeglumine (Gd-BOPTA) is a hepatobiliary-specific agent, it can be selectively taken up into function hepatocytes by the specific organic anion transporting polypeptides (OATP1B1, OATP1B3) located on the surface of hepatocytes ( 12 14 ). In addition to dynamic contrast-enhanced MRI of the liver, this agent may also assist with specific imaging in the hepatobiliary phase (HBP) within 40–120 min after injection ( 15 ).…”
Section: Introductionmentioning
confidence: 99%